Erratum to: Structural, Electromagnetic and Thermodynamic Analysis of Ion Pollutants Adsorption in Water by Gallium Nitride Nanomaterial: a Green Chemistry Application - Mollaamin, F.; Monajjemi, M. (Pleiades Publishing Ltd, 2024)
An Erratum to this paper has been published: https://doi.org/10.1134/S1990793124340037